Family adjustment and its relation to Self - affirmation among children in late delay childhood stage in the Damascus countryside governorate - Ez Elddin, Razzan Nadim (Al-Adab Journal, 2020)
The reason of this study is to reply the following inquiries: Are there any statistical significant correlations between Self Assertion and adjustment family among children . The sample of the study involves (300)child selected randomly (150) male child (150) female child with there mother of children in the delay childhood stage in the Damascus country governorate The researcher had used rating Self Assertion among children and adjustment family test. The researcher had used number statistical tests in ciuding:1-mean 2-the standard deviation 3-the correlation 4-t.test. The most important results of the current study are: There are strong statistical significant correlations between Self Assertion and adjustment family among children There are statistical significant differences in between Self Assertion males and females of low adjustment family children There are no statistical significant differences between Self Assertion males and females of high adjustment family children There are statistical significant differences in between Self Assertion older children and smaller children